2010
DOI: 10.1016/j.tetlet.2010.09.042
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of a tricyclic core of rameswaralide

Abstract: A tricyclic core containing a 5,7-fused bicyclic unit of rameswaralide was prepared starting from a 1,6-enyne. The synthetic sequence involved (i) ruthenium-catalyzed [5+2]-cycloaddition of 1,6-enyne, (ii) an acyl radical based approach to construct the lactone, and (iii) a regioselective installation of the conjugated double bond by a concomitant sulfenylation-dehydrosulfenylation sequence. KeywordsRuthenium; Cycloaddition; The fused bicyclic system; Reductive radical cyclization; Total synthesis Rameswaralid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
10
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 36 publications
1
10
0
Order By: Relevance
“…The collective studies of Trost ultimately enabled total syntheses of the marine norsesquiterpenoid frondosin A (Scheme ) and pseudolaric acid B (Scheme ), which displays activity against multidrug resistant cancer cell lines; in the latter synthesis, however, an analogous rhodium-catalyzed cycloaddition proved to be optimal for the (5+2) cycloaddition to form the core seven-membered ring. Synthetic studies toward the tricyclic core of rameswaralide also were disclosed (not shown) …”
Section: Seven-membered Ring Formationmentioning
confidence: 99%
“…The collective studies of Trost ultimately enabled total syntheses of the marine norsesquiterpenoid frondosin A (Scheme ) and pseudolaric acid B (Scheme ), which displays activity against multidrug resistant cancer cell lines; in the latter synthesis, however, an analogous rhodium-catalyzed cycloaddition proved to be optimal for the (5+2) cycloaddition to form the core seven-membered ring. Synthetic studies toward the tricyclic core of rameswaralide also were disclosed (not shown) …”
Section: Seven-membered Ring Formationmentioning
confidence: 99%
“…85 Synthetic access to core tricycle 278 would be accomplished by an acyl radical cyclization and epoxidation of selenide 279 (Scheme 62). Acylselenide 279 would be produced by the acylation of secondary alcohol 280.…”
Section: Synthetic Studies Toward Polycyclic Furanobutenolide-derimentioning
confidence: 99%
“…The potential anti-inflammatory activity and cytotoxicity toward A549 human lung carcinoma epithelial cells (IC 50 67 ± 3.7 μM) of rameswaralide ( 6 ) was also reported. Furthermore, with the exception of rameswaralide, the absolute stereochemistry of these diterpenoids has not yet been confirmed; however, it was indirectly assigned based on the established absolute stereochemistry of a probable biosynthetic precursor. , While several groups have pursued the synthesis of rameswaralide ( 6 ) and ineleganolide ( 5 ), which bear the 5,5,7 core (blue, Figure ), to our knowledge, there are no reported total syntheses. Less synthetic work has been directed to members possessing the 5,5,6 core (red) such as that found in yonarolide, scabrolides, dissectolides, and sinulochmodin C ( 1 – 4 ). …”
mentioning
confidence: 99%
“…We decided to set rameswaralide ( 6 ) as our initial target since it displays some of the most compelling bioactivity in this class of tetracyclic diterpenoids (Scheme ). Based on previous work by both Mehta and Trost, who independently synthesized a similar 5,5,7 core of rameswaralide, we anticipated that annulation of the D-ring would be challenging given the lack of further efforts toward this end. With this in mind, we proposed that α-halo enones such as enone 7 could serve as highly versatile intermediates for several D-ring annulation strategies toward rameswaralide ( 6 ).…”
mentioning
confidence: 99%
See 1 more Smart Citation